FEATURES OF WARFARIN INFLUENCE ON PLATELET FATTY ACID SPECTRUM IN ISCHEMIC HEART DISEASE PATIENTS WITH DIFFENT ATRIAL FIBRILLATION CLINICAL FORMS - Merkulova, I.O.; Lizogub, V.G.; Kramarova, V.N.; Bogdan, T.V. (The Ukrainian Scientific Medical Youth Journal, 2017)
Clinical protocols do not provide us an exact data about optimal scheme of anticoagulant therapy in patients with coronary artery disease (CHD) with atrial fibrillation (AF). It is known that warfarin directly affects fatty acids (FA) exchange in the body - potentiates the effect of omega-3 FA, and reduces the content of omega-6 FA. Although the effect of warfarin on the fatty acid spectrum (FAS) of platelet membranes phospholipids (PL) is still not fully understood. It was found that FAS PL platelets membranes of healthy people is characterized by the absence of myristic, pentadecanic, margarinic and linoleic FA. In patients with coronary heart disease compared to the control group (CG) there is a significant decrease in the relative content of stearic, arachidonic FA and a significant increase in the relative content of oleic acid in platelets PL membranes. In patients with CHD and AF, there is a significant decrease in the relative content of myristic, stearic, arachidonic FA, as well as a significant increase in the relative content of palmitic, oleinic and linoleic FA in PL platelet membranes, indicating the presence of structural changes in platelet membranes in patients with atrial fibrillation.To be one of the pathogenetic links of atrial fibrillation in these patients. Warfarin therapy in CHD with permanent AF patients led to a significant increase in the relative content of myristic (20,99%), stearic (15,17%) and arachidonic (34,04%) acids, which is a sign of cellular stabilization membranes, and in the presence of paroxysmal or persistent form of AF in PL membranes of platelets, the relative content of stearic acid increased (by 44.70%). Patients with coronary artery disease, in combination with a permanent form of AF, the appointment of a pharmacotherapy scheme that includes warfarin is more desirable because it leads to positive changes in the spectrum of PL membranes.